2003
DOI: 10.1046/j.1439-0442.2003.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent Relaxation of Canine Uterine Artery in Response to Acetylcholine: the Possible Involvement of Alternative Pathways

Abstract: The effect of acetylcholine on the isolated, pre-contracted, uterine artery of non-pregnant dog was investigated. Acetylcholine-induced concentration-dependent relaxation of isolated canine uterine artery with endothelium (pEC50 = 6.48 +/-0.01, n = 37) and was without effect on arterial segments denuded of endothelium. Indomethacin, 4-aminopyridine (10-5 m) and pre-contraction with K+-rich Krebs-Ringer bicarbonate solution had no effect on acetylcholine-induced relaxation. NG-nitro-l-arginine (l-NOARG) (10-5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(51 reference statements)
2
1
0
Order By: Relevance
“…This finding is in agreement with the studies of other authors (Matsumoto et al. , 1987, 1992) as well as with our previous report (Pesic et al. , 2003) where we suggested NO involvement in this acetylcholine‐induced effect.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in agreement with the studies of other authors (Matsumoto et al. , 1987, 1992) as well as with our previous report (Pesic et al. , 2003) where we suggested NO involvement in this acetylcholine‐induced effect.…”
Section: Discussionsupporting
confidence: 94%
“…Immunoreactive tenocytes are observed in a but not in b. TRITC staining. Bars 25 μm presumably being mediated by the endothelial production of nitric oxide (Pesic et al 2003). In accordance with several previous reports describing the location of muscarinic ACh receptors in blood vessel walls in other tissues (e.g., Badaut et al 1997), we have found M 2 R immunoreactivity to be mainly localized to the endothelial part of the vessels.…”
Section: Presence Of M 2 Immunoreactivity In Cells In Blood Vessel Wasupporting
confidence: 92%
“…In vitro canine experiments have demonstrated the importance of prostaglandins in regulating uterine vascular tone 37 . Additionally, in dogs, acetylcholine‐induced uterine artery vasodilatation probably occurs through the release of endothelium‐derived relaxing factors, such as nitric oxide, endothelium‐derived hyperpolarizing factor, and prostacyclin 38–40 . These vasodilator molecular pathways may contribute to explaining the RI and PI values found at the end of the study.…”
Section: Discussionmentioning
confidence: 89%